KOMPARASI EFISIENSI MATERIAL BAJA KARBON St 37, BAJA KARBON St 41 DAN BAJA KARBON St 60 TERHADAP LAJU KOROSI DI MEDIA AIR MUARA SUNGAI (PAYAU) DENGAN METODE ELEKTROKIMIA - Yusuf Nur Afandi; Sumarji Sumarji (ROTOR, 2013)
Mouth of the river is the meeting place of river water and sea water . water estuaries (brackish water) has asodium chloride content of between 1% -2.5 whether it's from natural sources around the surrounding river water or a mixture of sea water . many construction or structure that is attached to the mouth of the river environment made of metal materials, especially carbon  steel.  the use of  steel  in building  structures  in estuaries  susceptible  to  corrosion  due  to  environmental  water  containing  chemical  elements  that  are corrosive. Factors  affecting  corrosion  such  as  temperature,  acidity  (pH),  salinity  (NaCl),  the  levels  of chloride  (Cl),  the  levels of  sulfate  (SO) as well as dissolved oxygen, causing easily corroded carbon  steel. This study aims to determine the Comparative Efficiency of Steel St 37, St 41 Steel and Steel st 60 on the rate of corrosion  in aqueous media estuaries with  tool Potensiostat methods. This research  is an experimental laboratory to design the post-test group design. From the results obtained data show the results of corrosion rate measurements made  in  this study  that  the greatest rate of corrosion occurring on  the steel material St 37 is 29.527 mpy, St 41  steel was 27.548 mpy, and  steel St 60  is 24,493 mpy. The  results  showed  that  the corrosion rate of steel st 37 has a very large corrosion rate in comparison steel and carbon steel st 41 high st 60. From the observation  in micro on  the  trid specimen  three  is corrosion  that resembles a uniform or evenly corrosion. A  form of  corrosion  that  results  in a uniform attack on  the  entire  surface of  the metal. Keywords: Estuaries, The Rate of Corrosion